Volatility Spillover USD-IDR Exchange Rate With Indonesia Stock Price - Firdaus, Naupal Irfan; Dewi, Andrieta Shintia; Iradianty, Aldilla (TRIKONOMIKA, 2017)
Value of imports higher than exports, causing the trade deficit, the appreciation of the currency in the developed countries, and withdrawals by foreign investors on the Indonesian stock exchange market. These things cause the movement of the exchange rate USD-IDR and Indonesian Stock Price are volatile and tend to weaken in the period from January 3, 2011 - August 31, 2016. This study to determine spillover volatility of the exchange rate USD-IDR with Indonesian Stock Price. By using current time series data, analyzed by Augmented Dickey-Fuller (ADF), GARCH, and Granger Causality. The results of the data processing rate of USD-IDR and data Indonesian Stock Price stationary at first difference by changing the level of daily data into a return of the respective data. Data having problems heteroskedasticity so it can be analyzed using GARCH. Results of the analysis showed that there is a volatility spillover between the two data. Then granger causality test results show that the causality occurs in both directions, meaning that changes in the foreign exchange market to give effect to the capital markets, and vice versa.